2020
DOI: 10.9734/jenrr/2020/v4i230120
|View full text |Cite
|
Sign up to set email alerts
|

Production of Fuel Oil from Municipal Plastic Wastes Using Thermal and Catalytic Pyrolysis

Abstract: Plastics have become an essential part of modern life today. The global production of plastics has gone up to 299 million tonnes in 2013, which has increased enormously in the present years. The utilization of plastics and its final disposal pose tremendous negative significant impacts on the environment. The present study aimed to investigate the thermal and catalytic pyrolysis for the production of fuel oil from the polyethene plastic wastes. The samples collection for both plastic wastes and clay catalyst, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 12 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…As shown in Fig. 2, the recycling of plastic waste reduces the environmental burden and generates paths for further applications, such as the fabrication of value-added carbon materials (Chang et al, 2018;Chen et al, 2020a;Cho et al, 2019;Dankwah et al, 2018;Wen et al, 2019), fuels, aromatic chemicals (Miandad et al, 2018;Omol et al, 2020;Thahir et al, 2019), construction/cementitious materials Lahtela et al, 2019), polymers, and fibers Hu et al, 2019).…”
Section: Innovations In Particulate Plastic Waste Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Fig. 2, the recycling of plastic waste reduces the environmental burden and generates paths for further applications, such as the fabrication of value-added carbon materials (Chang et al, 2018;Chen et al, 2020a;Cho et al, 2019;Dankwah et al, 2018;Wen et al, 2019), fuels, aromatic chemicals (Miandad et al, 2018;Omol et al, 2020;Thahir et al, 2019), construction/cementitious materials Lahtela et al, 2019), polymers, and fibers Hu et al, 2019).…”
Section: Innovations In Particulate Plastic Waste Managementmentioning
confidence: 99%
“…At present, pyrolysis, catalytic steam reforming (Miandad et al, 2019;Omol et al, 2020), and hydrothermal technologies are emerging applications (Nabgan et al, 2017). The pyrolysisreforming method yields high H2, generally more than 30 g per 100 g of plastic waste (Barbarias et al, 2016).…”
Section: Fuels and Chemicals: Waste To Energymentioning
confidence: 99%
“…Recycling petroleum products such as polythene, PET bottles, and polypropylene into diesel can also be beneficial to the environment as well as increasing fuel supply in the country. This is attracting a number of researchers in the present days on how diesel fuel oil can be obtained from municipal plastic wastes, and it is efficient to use in transportation [ 191 ]. It can be concluded that the Uganda oil project is generally profitable and that deferring oil production is justified except in the cases where the net convenience yield or cost inflation is high [ 192 ].…”
Section: Petroleum Energymentioning
confidence: 99%
“…As one of the most popular bioenergy conversion technologies, thermal pyrolysis of carbon-rich biomass is unique because it produces bio-char in addition to biofuel. Omol et al [3] in their recent research work involving conversion of municipal plastic wastes to fuel oil also reported the pyrolysis process as an effective approach to achieving their research objective. Findings from studies of Mary et al [4] and Block et al [5] have highlighted the benefits of biochar technologies, particularly concerning carbon sequestration via land application of biochar.…”
Section: Introductionmentioning
confidence: 99%